Born wicked - Spotswood, Jessica (Spotswood, Jessica. Cahill witch chronicles, 2012)
In an alternate New England of 1900, where the Brotherhood dominates and controls society, sixteen-year-old Cate Cahill has struggled since her mother's death to keep secret that she and her younger sisters are witches, but when a governess arrives from the Sisterhood, everything changes.